Tissue Doppler systolic annular velocity and myocardial performance index as predictors of right ventricular affection and culprit lesion location in acute inferior myocardial infarction - Walaa Adel; Viola William; Mary Josef; Nagwa Al-Mahallawy (The Egyptian Heart Journal, 2014)
Aim: This study aims at using peak lateral tricuspid annular systolic velocity (ST) and right ventricular myocardial performance index (RV-MPI) as predictors of RV infarction (RVI) and subsequently localizing the culprit lesion in the proximal right coronary (RCA) rather than other locations [the distal RCA or dominant left circumflex (LCX) artery]. Patients: 30 patients suffering from acute inferior infarction, were subjected to early conventional and pulsed wave tissue Doppler echocardiographic examinations, measuring (ST) and calculating RV-MPI. Half of the patients had the culprit lesion proximal to the RV branch of the RCA and the other half had non-proximal RCA occlusion. Results: ST values were significantly reduced in patients with RVI. Cutoff value of ST was found to be 11.9 cm/s with a sensitivity 80.0%, specificity 93.3%, positive predictive value 92.3% and negative predictive value 82.4% in the identification of proximal RCA lesion as the culprit lesion. The calculated RV-MPI was significantly different; its mean value was 0.666 ± 0.118 in the proximal RCA vs. 0.524 ± 0.133 in the non-proximal RCA patients. RV-MPI cutoff value proved to be 0.50 with sensitivity 80%, specificity 66.7%, negative predictive value 76.9% and positive predictive value 70.6%. Conclusion: RVI caused by a proximal RCA lesion could be predicted using TDI to assess ST and RV-MPI from the tricuspid annulus. Patients with ST < 11.9 cm/s and RV-MPI ⩾ 0.5 indicated most probably occlusion of the proximal RCA.